Recent establishments and extinctions of Northern Gannet Morus bassanus colonies in North Norway, 1995-2008 - Barrett, Robert T. (Ornis Norvegica, 2008)
Since the last published review of the development of the Northern Gannet Morus bassanus population in Norway (Barrett & Folkestad 1996), there has been a general increase in numbers breeding in North Norway from ca. 2200 occupied nests in 1995 to ca. 2700 in 2008. In Lofoten and Vesterålen, however, numbers have decreased from 1500 occupied nests in 1989 to 500 in 2008, and what were the two largest colonies on Skarvklakken and Hovsflesa have been abandoned. Small colonies have, in the meantime, been established in the region, but these are all characteristically unstable. A new colony established in Troms in 2001 increased to 400 occupied sites in 2007, but the population dropped to 326 in 2008. Harassment by White-tailed eagles Haliaeetus albicilla is mooted as the main cause of the decline in Lofoten and Vesterålen.